2011
DOI: 10.1136/emermed-2011-200534
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous drinking among patients attending a minor injuries unit: a pilot study

Abstract: Excessive alcohol consumption increases the likelihood of accidental injury. This pilot study reports on the prevalence of hazardous drinkers presenting to a Minor Injuries Unit. The proportion of hazardous drinkers is broadly similar to that found in Emergency Departments, suggesting that such units could also host alcohol intervention and brief advice activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…to being asked about their alcohol intake" (Patton& Vohra, 2013), none of the clients withdrew from the study or shared negative views in or study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…to being asked about their alcohol intake" (Patton& Vohra, 2013), none of the clients withdrew from the study or shared negative views in or study.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study aimed to report the prevalence of hazardous drinking in patients attending a minor injury unit (Patton& Vohra, 2013). The authors observed that of the 70% of clients that presented at emergency department, 20% could be seen in a minor injury unit and more likely to get offered health related advice and information by emergency nurse practitioners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Department of Health (1999) stipulated health education and promotion to be a key feature for any organisation proposing to set up these new services, regardless, there is very little literature of how this feature has been upheld. Patton and Vohra (2013) conducted a 4 week pilot study on English speaking patients over the age of 16 that presented to a Minor Injuries Unit, to report on the prevalence of hazardous drinkers to determine if MIU's could host alcohol interventions and brief advice activities in units where clients would be seen by a nurse who is likely to offer advice compared of their medical colleagues. 192 participants in their study consumed alcohol at least double the daily recommended units or they admitted to presenting with an alcohol related injury or illness, 49% consumed at least double the recommended daily allowance in a single session with 34% admitting to drinking so much, more than once a week, 36% were identified as hazardous drinkers of which more were younger male, only 3% accepted the offer of help or advice.…”
Section: Gap In Services and Literature Reviewmentioning
confidence: 99%